Sosialisasi Perundungan di Medsos untuk Anak-Anak di RT04/03 Cipayung Jakarta Timur - Thertina, Erlis; Jepri, Jumadi; Edward, Ruben (CV Buana Prisma Sejahtera, 2025)
Bullying is an aggressive behavior that is intended to make someone feel frightened or angry, and it occurs frequently. The aim of this community service activity is to provide socialization on child bullying on social media in the form of community service which will provide knowledge and insight as well as the impact felt by victims of child bullying on social media so that children, parents and the community will be wiser in their words for the community. especially in Cipayung Village, East Jakarta. The activity began with a lecture and presentation of material about child bullying on social media and continued with an interactive discussion, then participants watched videos of child bullying on social media. Evaluation is carried out on the process which includes participants' attendance, enthusiasm/enthusiasm, and responses to socialization activities. The results of the service show that socialization activities have been able to increase knowledge and broaden people's insight in dealing with child bullying on social media. The evaluation results show response, enthusiasm, acceptance, attendance and and community participation in socialization activities is very good. By holding bullying outreach, parents and the community are able to monitor and deal with children's bullying on social media.